Nastrój a racjonalność myślenia w zależności od dominującego mechanizmu regulacji zachowania - Wróbel, Monika (Acta Universitatis Lodziensis. Folia Psychologica, 2007)
The article addresses the issue of the relationship between cognitive and affective processes, in particular mood and thinking. The aim of the study was to examine the relationship between mood and rational reasoning as well as the role of the systems of direct and indirect regulation of behaviour in this process. Two study groups (N = 51 and N = 53), a control group (N = 51) and a group of so-called “listening persons” (N = 104) took part in the study. The following measures were used: Mood Scale, Tasks Set, Questionnaire for Listening Person (the author’s techniques) and A. Kolańczyk’s AR Scale. The results show that those in whom negative mood was induced, solved tasks better and were more aware of their sensual experiences than those in whom positive mood was induced (which increased the awareness of reflections). However, the hypothesis that greater rationality of reasoning results from the interactive influence of both mood and systems of regulation of behaviour activity was not supported.